An analysis of the South African food and beverage industry efforts since 1994 in responding to major shifts in food consumption and mapping of the potential future applications of science and technology advances, to provide safe, affordable and nutritious foods - Ronquest-Ross, Lisa-Claire (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhDFoodSc)--Stellenbosch University, 2023.